2011
DOI: 10.4028/www.scientific.net/amm.143-144.125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rotor Inter-Turn Short-Circuit on Generator Rotor Force

Abstract: This paper analyzes the calculation method of unbalanced electromagnetic force by rotor winding inter-turn short-circuit fault, analytical calculating method neglects saturation, cogging and other factors, so the calculation accuracy is not high, in order to accurately calculate the magnetic field and the unbalanced electromagnetic force, this paper propose to analyze generator magnetic field by a finite element software Ansys, the obtained magnetic field data are further used to analyze the distributed electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…It is found that the induced voltage in rotor can be used to predict the location and the number of short circuit turns [23]. Meanwhile, researchers have also studied the characteristics of the excitation currents [24,25], the copper losses [24], and the unbalanced magnetic pull (UMP) for the interturn short circuit monitoring [15,26,27]. Generally, at present, the application of search coils, which is mainly based on the magnetic field density (MFD) variation, is still adopted as a primary approach to monitor and diagnose this fault [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the induced voltage in rotor can be used to predict the location and the number of short circuit turns [23]. Meanwhile, researchers have also studied the characteristics of the excitation currents [24,25], the copper losses [24], and the unbalanced magnetic pull (UMP) for the interturn short circuit monitoring [15,26,27]. Generally, at present, the application of search coils, which is mainly based on the magnetic field density (MFD) variation, is still adopted as a primary approach to monitor and diagnose this fault [28][29][30].…”
Section: Introductionmentioning
confidence: 99%